From face-to-face to online methodology. Analysis of families' perception of tele-school in of confinement. - Suberviola, Iratxe (Journal of Learning Styles, 2021)
The health alert caused by COVID-19 has forced schools to migrate from face-to-face education to online education, partial or total, depending on the moment.The educational community has had to adapt to this new situation in an almost improvised way.The study shows the results of an ad-hoc survey applied to more than 1500 Spanish families with sons and daughters between the educational stages of Early Childhood Education to High School. This study analyzes the perception of these families on factors such as: the perception of teacher preparation, the time spent by their children doing homework,, the children's competence to advance in studies, the availability of the necessary means and tools, the adaptation of the members of the family to the tele-school, studying the correlations according to the educational stage.
Keywords: Tele-school; confinement; family perception; COVID-19